Serum Amyloid A (SAA) induces transcription affecting inflammation - George H. Sack; Joseph Yun; C. Conover Talbot; Jasmeet Sethi (PLoS ONE, 2026)
The 104 aa protein Serum Amyloid A (SAA) is a prominent member of the acute phase response (APR) a remarkably conserved and stereotyped set of serum protein changes associated with inflammation and other stimuli. N-terminal fragments of SAA can form fibrils that accumulate in organs (where they are called “amyloidosis”). Recent reports have shown SAA involvement in inflammation, particularly with macrophages, consistent with its role as a “biomarker.” In contrast to this perception of passivity, we report that exposure to both N-terminal decapeptides and intact SAA monomers can induce multiple transcripts in both enteroids and HEK293 cells. The spectrum of transcripts prominently includes proteins related to inflammation and NF-κB control, specifically NFKB1A, TNFA1P3 and IER3. SAA thus can act directly through specific transcription to alter cellular physiology in cells outside the monocyte/macrophage lineage with direct effects on inflammation, likely helping explain its remarkable evolutionary conservation as part of primordial defense.